Efektivitas Program Keluarga Harapan Dalam Pengentasan Kemiskinan Di Kelurahan Sondakan - Indyra Bernice Azhary (Journal of Development and Social Change, 2025)
Poverty is a complex issue that requires sustainable handling strategies. The government has implemented the Conditional Cash Transfer program known as the Family Hope Program (PKH) to alleviate poverty by improving the quality of life of poor communities through better access to education, health, and social welfare services. This study aims to assess the effectiveness of PKH in reducing poverty in Sondakan Subdistrict, using four main indicators: target accuracy, program objectives, program socialization, and program monitoring. This research employs a qualitative method with a phenomenological approach. Data were collected through interviews, observations, and documentation. Robert K. Merton’s Functionalism structural theory is used to analyze the interrelation of elements within the social system, highlighting the function of each component in supporting the sustainability of PKH.The results show that the program is effective in terms of socialization, but less effective in target accuracy, goal achievement, and monitoring. Identified obstacles include dependency among beneficiaries, as well as administrative and system-related issues. The evaluation of these obstacles suggests the need for beneficiary education, administrative and system improvements, and enhanced support from program facilitators. The government also strives to improve program effectiveness through not only material support but also moral encouragement, graduation programs, and skills training to promote economic independence.